2023
DOI: 10.3389/fimmu.2023.1130662
|View full text |Cite
|
Sign up to set email alerts
|

The influence of high glucose conditions on macrophages and its effect on the autophagy pathway

Abstract: IntroductionMacrophages are central cells in mediating the inflammatory response.Objective and MethodsWe evaluated the effect of high glucose conditions on the inflammatory profile and the autophagy pathway in Bone-Marrow Derived Macrophages (BMDM) from diabetic (D-BMDM) (alloxan: 60mg/kg, i.v.) and non-diabetic (ND-BMDM) C57BL/6 mice. BMDM were cultured in medium with normal glucose (5.5 mM), or high glucose (25 mM) concentration and were primed with Nigericin (20µM) stimulated with LPS (100 ng/mL) at times o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 54 publications
(67 reference statements)
0
4
0
Order By: Relevance
“…The effect of hyperglycemia on the differentiation and activation of subpopulations of macrophages has previously been investigated. It was found that HG-treatment on M1 macrophages pre-stimulated with LPS led to increased secretion of pro-inflammatory cytokines [ 20 , 53 ], associated with an increase in ROS production and autophagy in macrophages. An HG environment also induced the secretion of pro-inflammatory cytokines during the differentiation of primary human macrophages [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of hyperglycemia on the differentiation and activation of subpopulations of macrophages has previously been investigated. It was found that HG-treatment on M1 macrophages pre-stimulated with LPS led to increased secretion of pro-inflammatory cytokines [ 20 , 53 ], associated with an increase in ROS production and autophagy in macrophages. An HG environment also induced the secretion of pro-inflammatory cytokines during the differentiation of primary human macrophages [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…; diabetes) are associated with the development of low-grade inflammation and macrophage infiltration and polarization inside metabolic tissues [ 19 ]. Indeed, it was shown that under high-glucose (HG) conditions M1 macrophages exhibited an amplified pro-inflammatory response and had decreased production of anti-inflammatory mediators leading to sustained inflammation [ 20 ]. During diabetes onset and progression, hyperglycemia increased ROS production in macrophages, which favor induction of M1 pro-inflammatory macrophages [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of hyperglycemia on the differentiation and activation of subpopulations of macrophages has previously been investigated. It was found that HG-treatment on M1 macrophages pre-stimulated with LPS led to increased secretion of pro-inflammatory cytokines [46, 47], associated with an increase in ROS production and autophagy in macrophages. An HG environment also induced the secretion of pro-inflammatory cytokines during the differentiation of primary human macrophages [48].…”
Section: Discussionmentioning
confidence: 99%